2013
DOI: 10.1007/s00228-013-1623-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of methotrexate in acute lymphoblastic leukaemia: why still at the bench level?

Abstract: Prospective pharmacogenetic studies which consider all of the above-mentioned factors should be undertaken to facilitate the design of personalized MTX treatment for ALL patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 41 publications
0
33
0
6
Order By: Relevance
“…92,93,95,96 Methotrexate There have been extensive pharmacogenetic studies of methotrexate in ALL. 97,98 Candidate-gene studies have focused on common variants in genes clearly involved in the folate pathway, such as MTHFR, SLC19A1, TYMS, and DHFR. 50,99 Despite multiple candidate-gene studies for toxicity, results have been conflicting (or based on single, nonreplicated small studies), and thus it is currently not possible to recommend changes to methotrexate dosing based on inherited variants in these candidate genes.…”
Section: Vincristinementioning
confidence: 99%
See 2 more Smart Citations
“…92,93,95,96 Methotrexate There have been extensive pharmacogenetic studies of methotrexate in ALL. 97,98 Candidate-gene studies have focused on common variants in genes clearly involved in the folate pathway, such as MTHFR, SLC19A1, TYMS, and DHFR. 50,99 Despite multiple candidate-gene studies for toxicity, results have been conflicting (or based on single, nonreplicated small studies), and thus it is currently not possible to recommend changes to methotrexate dosing based on inherited variants in these candidate genes.…”
Section: Vincristinementioning
confidence: 99%
“…50,99 Despite multiple candidate-gene studies for toxicity, results have been conflicting (or based on single, nonreplicated small studies), and thus it is currently not possible to recommend changes to methotrexate dosing based on inherited variants in these candidate genes. 97,98 Genome-wide studies identified variants associated with leukoencephalopathy, 100 but these findings have not yet been replicated. Methotrexate effects are influenced by interindividual variation in its plasma clearance, leading some to implement an approach that targets systemic exposure based on clearance.…”
Section: Vincristinementioning
confidence: 99%
See 1 more Smart Citation
“…It catalyzes the conversion of 5,10-methylene-tetrahydrofolate to 5-methyl-tetrahydrofolate, which serves as a methyl donor to convert homocysteine to methionine [71]. Two SNPs, C677T ( rs1901133 ) resulting in substitution of alanine with valine at codon 222 (Ala222Val) [72] and A1298C ( rs1801131 ) resulting in substitution of alanine for glutamic acid at codon 429 (Glu429Ala) [73] have been related to reduced activity of MTHFR and increased MTX level.…”
Section: Methotrexate (Mtx)mentioning
confidence: 99%
“…The outcome of ALL has improved significantly over the past six decades, with the 5-year survival rates increased from about 10-20 to 70-80 % [1][2][3]. There are about three phases in most chemotherapy protocols: induction, consolidation and maintenance [4]. And, methotrexate (MTX) is the key agent in most chemotherapy protocols.…”
Section: Introductionmentioning
confidence: 99%